The place of the individual in society - Goldman, Emma, 1869-1940 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Place of the Individual in Society" by Emma Goldman is a philosophical treatise written in the early 20th century. This work examines the intricate dynamics between the individual, society, and the state, engaging with themes of individuality, authority, and freedom. Goldman critiques existing political systems, arguing that true civilization is rooted in the liberation of the individual rather than in adherence to oppressive state structures. In this book, Goldman asserts that the state historically serves to suppress individuality and perpetuate economic and political inequalities. She emphasizes that real progress and cultural development stem from the individual$1 (Bs struggle against the constraints imposed by societal authorities. The text explores the tension between conformity and individuality, discussing how state power seeks to regiment and control human life while advocating for a society where individuals are free to express themselves and pursue their aspirations. Ultimately, Goldman proposes a vision of anarchism where society exists to serve the individual, promoting mutual aid and cooperation rather than authoritarian control. (This is an automatically generated summary.)s
Release date is 2023-08-16
Fritz Ohrenschall, Louise Pattison and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Individualism; Anarchism